Remote attestation scheme for cloud platform based on double-layer unbalanced hash tree - Xing RONG; Chang-xiang SHEN; Rong JIANG; Yong ZHAO (Tongxin xuebao)
In order to validate the service of cloud,an improved remote attestation scheme based on unbalanced hash tree of cloud platform was proposed.Double-layer unbalanced hash tree was built by introducing layer,original single tree was expanded to main tree and sub tree,which corresponded to virtual machine in cloud platform and the running components in virtual machine.Attestation needs no more than measurement component and authentication path.The analysis shows that this scheme can increase the attestation efficiency of cloud platform,and is good at protecting privacy and expandability,which is suitable for validating cloud platform service.